DSLR-Tutor: An Android Application for Essentials in Digital Photography - Jamingan, Azizan; Mahamad, Abd Kadir; Saon, Sharifah; Tuwoso; Iskandar, Ade Rahmat; Hapudin, Muhammad Soleh (Journal of Electronic Voltage and Application, 2020)
Modern camera of digital single-lens reflex (DSLR) comes with a variety of features to help the user get a better image quality. For professional photographers, many of them use manual mode to get better control over their camera. However, it may become difficult issue for beginner and amateur photographer as they need to know the basic knowledge of taking a photograph. For this reason, the Android application, DSLR-Tutor was developed to assist the beginner and amateur in digital photography to understand a few modes available for the camera as well as the important three basic rules, which are international standards organization (ISO), aperture and shutter speed. This DSLR- Tutor was developed using Android Studio v3.2.1. with a minimal configuration to set up the application. To give the user examples of the three basic rules combination, the application gives an example of a moving object image under bright daylight shot edited with various combination of the ISO, aperture and shutter speed. Results shows that the best combination of the ISO, aperture and shutter speed were, 640, 1/1.8 and 1/250, respectively. In conclusion, the DSLR-Tutor was able to help the beginner and amateur in digital photography to edit their photos accordingly and expected to be able to help them to use their camera confidently and take the best shot as possible.